2010
DOI: 10.4014/jmb.1002.02006
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Physiochemical Characterization of Melanin Pigment from Klebsiella sp. GSK

Abstract: A bacterium capable of producing melanin pigment in the presence of L-tyrosine was isolated from a crop field soil sample and identified as Klebsiella sp. GSK based on morphological, biochemical, and 16S rDNA sequencing. The polymerization of this pigment occurs outside the cell wall, which has a granular structure as melanin ghosts. Chemical characterization of the pigment particles showed then to be acid resistant, alkali soluble, and insoluble in most of the organic solvents and water. The pigment got bleac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 0 publications
11
66
0
Order By: Relevance
“…1B). These characteristics of absorption were consistent with the UVevisible absorption spectra of the melanins from fungi and bacteria (17,33,34). To confirm the paramagnetic properties and presence of free radicals of melanin, EPR analyses were performed (35).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…1B). These characteristics of absorption were consistent with the UVevisible absorption spectra of the melanins from fungi and bacteria (17,33,34). To confirm the paramagnetic properties and presence of free radicals of melanin, EPR analyses were performed (35).…”
Section: Resultsmentioning
confidence: 82%
“…The dark-brown water-soluble pigment from L. oligotrophicus was recovered from the culture by the modified method for bacterial melanin isolation (17). To identify the pigment, spectral (UVevisible, EPR and FT-IR) analyses were performed (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Santos and Stephanopoulos [5] and Muñoz et al [9] reported 375 mg/L and 6 g/L of extracellular melanin production, respectively, by recombinant E. coli . Sajjan et al [6] and Youngchim et al [48] have reported the production of intracellular melanin by Klebsiella sp . and Aspergillus fumigatus, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Plenty of literature is available regarding the synthesis and production of eumelanin by different bacteria [5, 6] and fungi [7, 8]. The production of melanin by recombinant E. coli under optimized submerged bioprocess was reported by Muñoz et al [9].…”
Section: Introductionmentioning
confidence: 99%